Reduced salt intake for heart failure: A systematic review - Mahtani, K; Heneghan, C; Onakpoya, I; Tierney, S; Aronson, J; Roberts, N; Hobbs, F; Nunan, D (American Medical Association, 2018)
Importance Recent estimates suggest that more than 26 million people worldwide have heart failure. The syndrome is associated with major symptoms, significantly increased mortality, and extensive use of health care. Evidence-based treatments influence all these outcomes in a proportion of patients with heart failure. Current management also often includes advice to reduce dietary salt intake, although the benefits are uncertain. Objective To systematically review randomized clinical trials of reduced dietary salt in adult inpatients or outpatients with heart failure. Evidence Review Several bibliographic databases were systematically searched, including the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, and CINAHL. The methodologic quality of the studies was evaluated, and data associated with primary outcomes of interest (cardiovascular-associated mortality, all-cause mortality, and adverse events, such as stroke and myocardial infarction) and secondary outcomes (hospitalization, length of inpatient stay, change in New York Heart Association [NYHA] functional class, adherence to dietary low-salt intake, and changes in blood pressure) were extracted. Findings Of 2655 retrieved references, 9 studies involving 479 unique participants were included in the analysis. None of the studies included more than 100 participants. The risks of bias in the 9 studies were variable. None of the included studies provided sufficient data on the primary outcomes of interest. For the secondary outcomes of interest, 2 outpatient-based studies reported that NYHA functional class was not improved by restriction of salt intake, whereas 2 studies reported significant improvements in NYHA functional class. Conclusions and Relevance Limited evidence of clinical improvement was available among outpatients who reduced dietary salt intake, and evidence was inconclusive for inpatients. Overall, a paucity of robust high-quality evidence to support or refute current guidance was available. This review suggests that well-designed, adequately powered studies are needed to reduce uncertainty about the use of this intervention.